Anti-Ro52/TRIM21 is independently associated with pulmonary arterial hypertension and mortality in a cohort of systemic sclerosis patients. (2nd November 2021) - Lee, AYS; Patterson, KA; Tan, DJ; Wilson, ME; Proudman, SM; Stevens, W; Nikpour, M; Sahhar, J; Ngian, G-S; Roddy, J; Roberts-Thomson, PJ; Walker, JG
Abstract : Objective : We undertook a comprehensive cross-sectional analysis of a multicentred Australian cohort of systemic sclerosis (SSc) patients to evaluate the associations of anti-Ro52/TRIM21 with SSc pulmonary involvement. Method : The study included 596 patients from the Australian Scleroderma Cohort Study database whose anti-Ro52/TRIM21 status was known. Anti-Ro52/TRIM21 was measured via line immunoassay. Data on demographic variables, autoantibody profiles, presence of interstitial lung disease (ILD), presence of pulmonary arterial hypertension (PAH), oxygen saturation, Six-Minute Walk Test distance, Borg dyspnoea score, and lung function tests were extracted. SPSS software was used to examine associations using univariate and multivariate analyses. Results : Anti-Ro52/TRIM21 was present in 34.4% of SSc patients. In the cross-sectional analysis, anti-Ro52/TRIM21 was independently associated with PAH [odds ratio 1.75, 95% confidence interval (CI) 1.05–2.90], but not ILD or other surrogate measures of pulmonary involvement such as average patient oxygen saturation. The antibody, however, was also associated with a higher forced vital capacity/diffusing capacity of the lung for carbon monoxide ratio. Prospectively, anti-Ro52/TRIM21 was also associated with an increased risk of death in patients with SSc (hazard ratio 1.62, 95% CI 1.11–2.35), independent of confounding factors. The primary cause of death appeared to be related to PAH and/or ILD, and anti-Ro52/TRIM21 was associated with PAH-related complications. Conclusion : Anti-Ro52/TRIM21 was independently associated with PAH and mortality in SSc patients. Future longitudinal studies are recommended to investigate the timing and pathogenic mechanisms of this autoantibody in PAH.